2019
DOI: 10.1002/jee.20251
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of student team dynamics between nonflipped and flipped versions of a large‐enrollment sophomore design engineering course

Abstract: Background: This study examined the differences between team dynamics in nonflipped and flipped versions of a multisection team-and project-based sophomore engineering design course. Purpose/Hypothesis: We hypothesized that team dynamics in nonflipped and flipped course settings may reveal differences in student perceptions of team conflict, peer assessment, and team member satisfaction as well as possible relationships among these three variables. Design/Method: Students in both nonflipped and flipped setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…The US Accreditation Board of Engineering and Technology defines a team as a group of individuals of diverse backgrounds, skills, and perspectives, working together toward a common goal (ABET 2016-17). The ability to work effectively as an engaged member of a team, is among the top most important behaviour attributes needed for engineers (ABET 2016-17;Baughman, Hassall, and Xu 2019;Usher and Barak 2018). In engineering courses, working on team projects involving authentic industrial problems is a well-known practice (Barak and Usher 2020;Chen, Kolmos, and Du 2020).…”
Section: Teamwork and Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…The US Accreditation Board of Engineering and Technology defines a team as a group of individuals of diverse backgrounds, skills, and perspectives, working together toward a common goal (ABET 2016-17). The ability to work effectively as an engaged member of a team, is among the top most important behaviour attributes needed for engineers (ABET 2016-17;Baughman, Hassall, and Xu 2019;Usher and Barak 2018). In engineering courses, working on team projects involving authentic industrial problems is a well-known practice (Barak and Usher 2020;Chen, Kolmos, and Du 2020).…”
Section: Teamwork and Innovationmentioning
confidence: 99%
“…Teamwork can provide engineering students with a realistic and complex industry-like experience that they are likely to encounter during their professional lives. However, the application of effective teamwork has many challenges (Baughman, Hassall, and Xu 2019;Tseng and Yeh 2013;Usher and Barak 2020). One major challenge is the composition of team members.…”
Section: Teamwork and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these, many countries give special attention to courses involving technology in the training of pre-service teachers because they are the individuals who will educate students having different learning styles, motivation, and pre-requisite knowledge to be able to survive in modern society as being reflective, critical, selfdirected learners and good at the use of technology. In this sense, flipped learning was proposed as an active teaching-learning approach to meet the learning needs of nextgeneration students (Baughman, Hassall & Xu, 2019;Castedo, Lopez, Chiquito, Navarro, Cabrera & Ortega, 2019;Maycock, Lambert & Bane, 2018;Ziegelmeier & Topaz, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Asio, Cross, and Ekwaro-Osire [57] found that the perception of teams' innovation differs based on teams' cohesion, conflict, and psychological safety. Teams in flipped classrooms have more satisfaction than non-flipped classroom teams, but they have similar levels of conflict [58]. Albeit psychological safety is a very important team dynamic for increasing team learning and can be used as a proxy for other team dynamics [59], [60], there is a gap in engineering education research to address psychological safety.…”
Section: Teamwork In Engineering Education Literaturementioning
confidence: 99%